Upaya Peningkatan Produktivitas Kebun Strowberi,Koloni Lebah dan Produksi Madu di Kabupaten Rejang Lebong Provinsi Bengkulu - Saepudin, Rustama (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2016)
This study aimed to evaluate the strawberry productivity, the development of bee colony and production of honey bee colonies in the strawberry plantation (Fragaria sp) at agrotourism area in Karang Jaya subdistrict Selupu Rejang Rejang Lebong. Fifteen stup honeybees which are imported from the island of Java were placed at the strawberry plantation. The research variables include the development of the colony, honey production, strawberry production, and supporting variables. The data obtained are presented in tables, figures and analyzed descriptively. Research outputs indicate that the development of bee colonies and honey production were still above average and there was no differences between bees which were placed in strawberry plantation and those were placed far from strawberry. The honey production at strawberry plantation was relatively lower. In contrary, the production of strawberries was higher fromthe average value of 25.55 kg/ha/yieldto 30.8 kg/ha/yield.